2019
DOI: 10.1002/anie.201905137
|View full text |Cite
|
Sign up to set email alerts
|

Poly(arylenevinylene)s through Ring‐Opening Metathesis Polymerization of an Unsymmetrical Donor‐Acceptor Cyclophane

Abstract: Reported are well-defined donor-acceptor alternating copolymers prepared using ring-opening metathesis polymerization (ROMP). Unsymmetrical cyclophanedienes comprising electron-donating (4-methoxy-1-(2-ethylhexyl)oxy)benzene( MEH) and electron-accepting benzothiadiazole (BT) rings were synthesized from the corresponding [3.3]dithiaparacyclophanes.R OMP of the strained unsymmetrical and "electronically-ambiguous" cyclophanedienes proceeded in ac ontrolled manner in the presence of either Hoveyda-GrubbsI Io rG r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 28 publications
(54 reference statements)
0
32
0
Order By: Relevance
“…Upon initiator screening for MEH-BT, we found that polymerizations initiated by Grubbs II and Hoveyda-Grubbs II yielded the highest conversions. 7 Specifically, ROMP of -OEH eclipsed 9b led to 100% conversion, whereas -OMe eclipsed 9a optimized at 75% conversion. We attributed the higher relative reactivity of (9b) to a lessened steric crowding with the -OEH exogenously eclipsed with BT, which exposes the 'backside' of the monomer for CM to occur more efficiently.…”
Section: Scheme 6 Schematic Depicting Design For Donor-acceptor-sequementioning
confidence: 98%
See 4 more Smart Citations
“…Upon initiator screening for MEH-BT, we found that polymerizations initiated by Grubbs II and Hoveyda-Grubbs II yielded the highest conversions. 7 Specifically, ROMP of -OEH eclipsed 9b led to 100% conversion, whereas -OMe eclipsed 9a optimized at 75% conversion. We attributed the higher relative reactivity of (9b) to a lessened steric crowding with the -OEH exogenously eclipsed with BT, which exposes the 'backside' of the monomer for CM to occur more efficiently.…”
Section: Scheme 6 Schematic Depicting Design For Donor-acceptor-sequementioning
confidence: 98%
“…We envisioned that a monomer system incorporating both donor and acceptor moieties could preorganize D-A dyads with electronic bias dictating sequencing (Scheme 6). 7 Whereas KCTP still does not demonstrate a purely electronically biased polymerization, other polymerization methods initiated by metals should be capable of featuring bias. In contrast to KCTP, the ring-opening metathesis polymerization of strained cycloalkenes is likely to exhibit both steric and electronic bias in concert, given metallacyclobutane formation is driven by both factors.…”
Section: Synpacts Syn Lett 5 Electronically Governed Sequence Controlmentioning
confidence: 99%
See 3 more Smart Citations